2018
DOI: 10.11604/pamj.2018.30.152.12046
|View full text |Cite
|
Sign up to set email alerts
|

Psychomotor regression due to vitamin B12 deficiency

Abstract: A vitamin B12 deficiency in infants is rare, but may sometimes be seen in breastfed babies of strict vegetarian mothers. Vitamin B12, also known as cobalamin, is only found in meat and other animal products. Most babies have a sufficient supply as long as the mother was not deficient herself. Symptoms and signs of vitamin B12 deficiency appear between the ages of 2 to 12 months and include vomiting, lethargy, failure to thrive, hypotonia, and arrest or regression of developmental skills. Urinary concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 22 publications
0
16
0
3
Order By: Relevance
“…Solid arrow lines illustrate well-documented links, whereas dotted arrow lines show links that remain to be confirmed by further studies. Animal derived food (eg, raw liver of beef, pork, or chicken, fish, and shellfish); plant derived food 37 Deficiency related to muscle and neurological dysfunctions, ↓ energy and exercise tolerance 35,38,39 Vitamin K2 (menaquinones)…”
Section: ↓ Intesɵnal Healthmentioning
confidence: 99%
“…Solid arrow lines illustrate well-documented links, whereas dotted arrow lines show links that remain to be confirmed by further studies. Animal derived food (eg, raw liver of beef, pork, or chicken, fish, and shellfish); plant derived food 37 Deficiency related to muscle and neurological dysfunctions, ↓ energy and exercise tolerance 35,38,39 Vitamin K2 (menaquinones)…”
Section: ↓ Intesɵnal Healthmentioning
confidence: 99%
“…Studies on protein malnutrition have demonstrated increased hippocampal expression of trkB & GAP-43 protein, indicating increased stress response (11). In addition to macronutrients, deficiencies in micronutrients, including vitamins, are implicated in a variety of disorders and delayed recovery mechanisms (12). Vitamin B12 which is essential in the conversion of homocysteine to methionine via methionine synthase for DNA and RNA synthesis (13), produces a large number of biological agents, including the myelin sheath.…”
Section: Malnutrition and Neurological Disordersmentioning
confidence: 99%
“…A relação da vitamina B12 materna com o da sua prole destaca o papel crucial de gestação para prevenir a deficiência de B12 na próxima geração. É importante ressaltar que há diretrizes para a fortificação de farinha com B12 desenvolvidas pela Food Fortification Initiative 36,37 e aprovadas pela Organização Mundial de Saúde (OMS). Além disso, como a farinha na maioria dos países agora é fortificada com ácido fólico, a cofortificação com B12 eliminaria qualquer uma das preocupações, ainda controversas, sobre o alto nível de folato exacerbar a deficiência de B12 38,39 .…”
Section: Prevenção Da Deficiência De Vitamina B12unclassified